2017
DOI: 10.1073/pnas.1702192114
|View full text |Cite
|
Sign up to set email alerts
|

Methylcytosine dioxygenase TET3 interacts with thyroid hormone nuclear receptors and stabilizes their association to chromatin

Abstract: Thyroid hormone receptors (TRs) are members of the nuclear hormone receptor superfamily that act as ligand-dependent transcription factors. Here we identified the ten-eleven translocation protein 3 (TET3) as a TR interacting protein increasing cell sensitivity to T3. The interaction between TET3 and TRs is independent of TET3 catalytic activity and specifically allows the stabilization of TRs on chromatin. We provide evidence that TET3 is required for TR stability, efficient binding of target genes, and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…We focused on TET3 because of its high expression in hepatocytes (Fig. A,B) and its known interactions with another nuclear receptor family member, thyroid hormone receptor alpha 1 . Of note, TET3 co‐immunoprecipitation with HNF4A in HepG2 cells, which express high levels of both HNF4A and TET3, confirmed that the two proteins interact (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We focused on TET3 because of its high expression in hepatocytes (Fig. A,B) and its known interactions with another nuclear receptor family member, thyroid hormone receptor alpha 1 . Of note, TET3 co‐immunoprecipitation with HNF4A in HepG2 cells, which express high levels of both HNF4A and TET3, confirmed that the two proteins interact (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…TET2 and TET3 are known to be required for this 5mC oxidation process in hepatocytes . Here, we focused on TET3 because it is more highly expressed compared to other TETs in liver and is known to interact with other TFs . Given that TET2 is also expressed in liver, HNF4A may also interact with TET2 in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Besides being the key intermediate for TET-mediated DNA demethylation, 5hmC is a potential epigenetic mark; yet, the exact rules that govern how and when TETs proceed beyond 5hmC leading to DNA demethylation are unclear. Recently, non-catalytic functions of TETs have also been described [10][11][12][13] . Mechanistically, TETs as general DNA-binding proteins appear to be recruited to specific gene loci by transcription factors.…”
mentioning
confidence: 99%
“…Possible mechanisms of locus-specific 5hmC changes are guided by factors like transcription factors (TF), TET binding proteins, Polycomb Repressive complex 2 (PRC2), histone modifications and post-translational modifications of TFs (Figure 2). TFs like HIF1, thyroid hormone nuclear receptors, retinoic acid receptor (RAR), etc., are shown to interact with TET1 and thus demethylate their target genes by 5hmC [84,[113][114][115]. Apart from TFs, TET-interacting proteins can also recruit it to a particular locus.…”
Section: -Hydroxymethylcytosine Changes Are Locus-specificmentioning
confidence: 99%